The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.ijid.2019.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Severe Bordetella pertussis infection and vaccine issue in Chongqing, from 2012 to 2018

Abstract: Objective: Pertussis is a highly contagious respiratory illness mainly caused by the Gram-negative bacterium Bordetella pertussis. The infection of B. pertussis has been increasing and the current diagnosis of pertussis in children is challenging; little is known of B. pertussis infection in Chongqing. Methods: There were 25,441 children (14,863 male and 10,578 female) with suspected pertussis enrolled in our retrospective study from December 2012 to November 2018. Then 800 children with suspected B. pertussis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Fifth, prior studies reported that new B. pertussis strains different from that included in the present vaccines have emerged 47 , 51 , which may have effect on the manifest rebound of pertussis infections. Sixth, a recent research found that the proportion of the reported pertussis cases aged 1–5 and over 5 years have increased about 4 folds and the proportion aged 3–12 months reduced from 70.59 to 58.39% from 2013 to 2018, respectively, in Chongqing, which can be ascribed to the unqualified vaccine quality 44 , 52 . Finally, weather parameters may also play an important role in the manifest rebound of pertussis infections, as evidenced by the findings of our study and others 14 , 24 26 , and it can also be seen from the data in Table S4 that the monthly aggregate precipitation and average wind velocity showed a higher level during the period 2016–2018 as compared to that during the period 2004–2015, while the monthly average air pressure displayed a lower level during the period 2016–2018 relative to the level during the period 2004–2015.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifth, prior studies reported that new B. pertussis strains different from that included in the present vaccines have emerged 47 , 51 , which may have effect on the manifest rebound of pertussis infections. Sixth, a recent research found that the proportion of the reported pertussis cases aged 1–5 and over 5 years have increased about 4 folds and the proportion aged 3–12 months reduced from 70.59 to 58.39% from 2013 to 2018, respectively, in Chongqing, which can be ascribed to the unqualified vaccine quality 44 , 52 . Finally, weather parameters may also play an important role in the manifest rebound of pertussis infections, as evidenced by the findings of our study and others 14 , 24 26 , and it can also be seen from the data in Table S4 that the monthly aggregate precipitation and average wind velocity showed a higher level during the period 2016–2018 as compared to that during the period 2004–2015, while the monthly average air pressure displayed a lower level during the period 2016–2018 relative to the level during the period 2004–2015.…”
Section: Discussionmentioning
confidence: 99%
“…The exact reasons why the rapid increase in the notified numbers of pertussis in recent years failed to be completely clarified in Chongqing; however, several plausible factors may drive such a rise. First, the use of advanced diagnostic methods with higher sensitivity such as simultaneous amplification and testing (SAT), real-time PCR and serologic has improved the recognition of some mildly or moderately infected individuals, especially for people without typical clinical symptoms 4,44 . Second, the medical professionals have enhanced their awareness of the diagnosis and report of pertussis in that this disease was designated as a notifiable infectious disease in China 3,12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, exosomes and OMVs derived from bacteria have been reported to be potent immune modulators, rather than aiding pathogenesis (163). The potential of OMVs as immune activators has been investigated using models of different infectious diseases such as pertussis (whooping cough), which is caused by Bordetella pertussis, a gram-negative bacterium (164). Currently available vaccines aid the successful reduction of the morbidity and mortality caused by pertussis, but they are also associated with severe adverse effects and weak immune protection (165).…”
Section: Exosome-based Immunization Strategy For Non-viral Infectious Diseasesmentioning
confidence: 99%